EVALUATION OF ASSOCIATION BETWEEN ASTHMA AND VITAMIN D DEFICIENCY IN CHILDREN AND ADULT: PROSPECTIVE OBSERVATIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Asthma is a chronic inflammatory airway disease with variable severity and control. Recent evidence suggests a potential role of vitamin D deficiency in influencing asthma outcomes. The aim of the study is to evaluate the association between vitamin D deficiency and asthma severity, control, and lung function in children and adults. Materials and Methodology: This prospective observational study included 100 patients with bronchial asthma attending a tertiary care hospital. Serum 25-hydroxyvitamin D levels were measured and categorized as deficient, insufficient, or sufficient. Asthma severity was assessed using GINA guidelines, and control was evaluated using the Asthma Control Test (ACT). Pulmonary function tests were performed to assess FEV1, FVC, and FEV1/FVC ratio. Statistical analysis was performed using chi-square test, ANOVA, and correlation analysis. Results: Vitamin D deficiency was observed in 52% of patients. A significant association was found between vitamin D status and asthma severity (p = 0.001) as well as asthma control (p = 0.002). Patients with vitamin D deficiency had significantly lower lung function parameters (p < 0.001). Positive correlation was observed between vitamin D levels and FEV1 and ACT score, while a negative correlation was noted with asthma severity. Conclusion: Vitamin D deficiency is highly prevalent in asthma patients and is significantly associated with increased severity, poor control, and reduced lung function. Assessment of vitamin D status may be beneficial in the comprehensive management of asthma.